2009
DOI: 10.1590/s0100-40422009000600014
|View full text |Cite
|
Sign up to set email alerts
|

Perfil espacial e temporal de poluentes nas águas da represa municipal de São José do Rio Preto, São Paulo, Brasil

Abstract: Cristóvão Colombo, 2265, 15054-000 São José do Rio Preto -SP, BrasilRecebido em 10/6/08; aceito em 9/2/09; publicado na web em 3/7/09 SEASONAL AND SPATIAL TREND OF POLLUTANTS IN THE WATERS OF THE SÃO JOSÉ DO RIO PRETO MUNICIPAL DAM, SÃO PAULO STATE, BRAZIL. In this manuscript, seasonal and spatial trends of water collected from two sampling places in the Preto River in the Turvo-Grande watershed were evaluated. Water samples were collected during June/07 to July/08 and parameters sulphate, total organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
1
2
0
2
Order By: Relevance
“…Similar behavior has also been observed in different rivers in Brazil (MELO et al, 2009;MEDEIROS et al, 2011).…”
Section: Concentration Of Total Solidssupporting
confidence: 86%
“…Similar behavior has also been observed in different rivers in Brazil (MELO et al, 2009;MEDEIROS et al, 2011).…”
Section: Concentration Of Total Solidssupporting
confidence: 86%
“…Thus, the oxic layers of sediment were thickest in CAPRP, followed by RTURARG and then RGRANDE. This pattern may be due to the shallow depth of CAPRP (0.5-3.0 m) relative to the other aquatic bodies (25-100 m), which provides no stratification of dissolved oxygen in the water column (Melo et al 2009) and may increase oxygenation of the sediment. In the TGDB rivers, the peak concentrations of Mn were above those of Fe and may be attributed to the more thermodynamically favorable reduction of Mn (Metzger et al 2007;Santos-Echeandia et al 2009).…”
Section: Sediment Characteristicsmentioning
confidence: 99%
“…4 shows that temporal variation. In summary, low HIs occur more frequently in summer or autumn, spring or winter usually have relatively lower HIs, since is self-evident that the pollutants are more easily concentrated in the low-flow periods (Melo et al, 2009). A previous study also showed that the seasonal variations in the river water quality with respect to heavy metals contamination (Reza and Singh, 2010).…”
Section: Concentration Of Metals In Groundwatermentioning
confidence: 78%